1999
DOI: 10.1002/(sici)1097-4695(19991105)41:2<189::aid-neu3>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the Drosophila ellipsoid body neuropil: Organization and development of the central complex

Abstract: The central complex is an important center for higher-order brain function in insects. It is an intricate neuropil composed of four substructures. Each substructure contains repeated neuronal elements which are connected by processes such that topography is maintained. Although the neuronal architecture has been described in several insects and the behavioral role investigated in various experiments, the exact function of this neuropil has proven elusive. To describe the architecture of the central complex, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(140 citation statements)
references
References 23 publications
8
132
0
Order By: Relevance
“…The ellipsoid body contains ten types of small-field neurons that connect it to other central complex substructures (for example, the fan-shaped body) 13 . It also contains at least six types of large-field (R) neurons that arborize as a ring, mainly in the anterior part 13,28 . Genetic mosaic flip-out analyses and immunolabeling indicated that the dNR2-positive neurons are the large-field, R4m subtype (H.-H. Lin, and A.-S.C., unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…The ellipsoid body contains ten types of small-field neurons that connect it to other central complex substructures (for example, the fan-shaped body) 13 . It also contains at least six types of large-field (R) neurons that arborize as a ring, mainly in the anterior part 13,28 . Genetic mosaic flip-out analyses and immunolabeling indicated that the dNR2-positive neurons are the large-field, R4m subtype (H.-H. Lin, and A.-S.C., unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…The EB is organized in a concentric pattern of glomeruli with major contributions from the projections of large-field ring or R neurons (Fig. 4C) (40,41). A subgroup of these, the R2/R4 EB neurons, mediate both ethanolinduced hyperactivity (33) and ethanol tolerance (42,43).…”
Section: Different Subsets Of Dopamine Neurons Drive Competing Behavimentioning
confidence: 99%
“…8 E). The ellipsoid body precursor, a flat neuropilic structure consisting of dorsal fibers, elongates downward during metamorphosis to form the final adult ring shape (Renn et al, 1999;Boquet et al, 2000). Thus, we believe the phenotype observed in vav mutants is most likely due to ellipsoid body neurons failing to achieve complete growth.…”
Section: Vav Is Required For the Correct Growth Of Axons Forming The mentioning
confidence: 99%